An Uncommon Site of Streptococcus pneumoniae Colonization Leading to Recurrent Pneumococcal Disease. (7th December 2016) - Sendi, Parham; Moser Schaub, Eva Maria; Nirgianakis, Konstantinos; Hathaway, Lucy J.; Bittel, Pascal; Goldblatt, David; Streit, Sven
Abstract: This report describes a case of relapsing pneumococcal peritonitis. The postulated source of infection was vaginal colonization and secondary adherence of pneumococci to an intrauterine contraceptive device. After immunization with a conjugate pneumococcal vaccine, her antibody levels were observed. She remained infection free at the 2-year follow-up investigation.